(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Household waste management and low health awareness are persistent challenges for sustainable development in Indonesia. While waste-sorting programs exist, their integration with clinical health monitoring remains underexplored. This study evaluates a community service program in Cikoneng Kulon Village (2025) that integrates the Zero Waste concept—specifically the TOSADA (Kitchen Waste Bin) and Rocket Stove technologies—with Free Health Screenings (FHS). Using a participatory educational approach with 155 participants and pre/post-test evaluations from 20 purposively selected respondents, the study measured changes in knowledge and behavioral intent. Results indicated a substantial improvement in technical knowledge; understanding of TOSADA increased from 35% to 85%, and Rocket Stove utility from 30% to 80%. Furthermore, 90% of respondents expressed a willingness to adopt daily Zero Waste habits. The integration of clinical health screenings acted as a primary driver for community participation, proving that a holistic approach can foster sustainable behavioral change in both environmental and public health domains.